Exploring Candesartan, an angiotensin II receptor antagonist, as a novel inhibitor of NLRP3 inflammasome: alleviating inflammation in Neisseria gonorrhoeae infection - Wen-Yu Lin; Jin-Lian Tsui; Hsiao-Wen Chiu; Wei-Ting Wong; Chun‑Hsien Wu; Hsien-Ta Hsu; Chen-Lung Ho; Shan-Pei Yeh; Yerra Koteswara Rao; Ann Chen; Chien-Chun Wang; Chung-Hua Hsu; et al. (BMC Infectious Diseases, 2024)
Abstract Background Gonorrhea, induced by Neisseria gonorrhoeae infection, stands as a prevalent sexually transmitted inflammatory disease globally. Our earlier research illuminated that N. gonorrhoeae-infected macrophages provoke inflammation by activating the intracellular sensor NACHT, LRR, and PYD domain-containing protein 3 (NLRP3) inflammasome, a pivotal regulator in inflammatory diseases governing the maturation and secretion of interleukin (IL)-1β and IL-18. Nevertheless, effective therapies addressing N. gonorrhoeae-mediated NLRP3 inflammasome activation and ensuing inflammation are currently lacking. This study delves into the impact of the angiotensin II receptor antagonist Candesartan (CS) on N. gonorrhoeae-infected macrophages. Methods The protein expression levels were examined through ELISA and Western blotting. Intracellular H2O2 levels, mitochondrial reactive oxygen species, and mitochondrial membrane integrity were evaluated using targeted fluorescent probes and analyzed via flow cytometry. NF-κB transcriptional activity was assessed using NF-κB reporter cells. LC3-knockdown cells were created using CRISPR/Cas9 technology. Results CS effectively inhibits the NLRP3 inflammasome, as indicated by the suppression of caspase-1 activation, IL-1β secretion, NLRP3 release, and the release of apoptosis-associated speck-like protein containing a CARD (ASC) in N. gonorrhoeae-infected J774A.1 macrophages. Additionally, CS selectively impedes IL-6 secretion and iNOS expression in both N. gonorrhoeae-infected J774A.1 and RAW264.7 macrophages. Mechanistic insights uncover the inhibition of NF-κB by CS in N. gonorrhoeae-infected J774A.1 macrophages, while intracellular H2O2 generation, mitogen-activated protein kinases phosphorylation, and mitochondrial damage remain unaffected. Notably, our study highlights that CS-induced autophagy contributes partially to its inhibitory effect on the NLRP3 inflammasome. Conclusions These results underscore the potential of CS as an anti-inflammatory drug for the treatment of gonorrhea, addressing a critical unmet medical need in combating N. gonorrhoeae-induced inflammation.